Estudo das propriedades estímulo responsivas dos polímeros escovas - Sempionatto, Juliane Renata [UNESP] (2015)
This study describes the production and characterization of polymer brushes thin films build on indium tin oxide substrate (ITO) in order to study the stimuli-responsive properties that lead to structural changes of the films. To characterize the surfaces atomic microscopy, energy dispersive X-ray and atomic force microscopy techniques were used. The influence of pH and ionic strength were evaluated by electrochemical methods and localized surface plasmon resonance (L-SPR). The polymers ply (acrylic acid) - (PAA), poly (2-vinyl pyridine) - (P2VP), poly (2-dimethyl amino ethyl methacrylate) (PDMAEMA) and the mixture P2VP with PAA were used to construct the brush films. Electrochemical tests showed a dependence of the polymer brushes conformation with ionic strengh and pH. P2VP and PDMAEMA had better response at acidic pH, since the polymer chains were extended and positively charged, allowing the diffusion of the negatively charged redox species through the film to the electrode surface. Not intituitively, PAA polymer film also showed a better amperometric response in acid pH, when their chains were collapsed on the surface. This curious response was because the redox species used in the tests were charged negatively, occurring thus electrostatic repulsion between the PAA negatively streched chains (basic pH) and the negatively charged redox specie, thus leading to a major signal in acidic pH where the PAA brushes were neutral. The results obteined by electrochemistry were corroborated usign L-SPR assays. It was also possible to obtain the sensitivity value due to pH variation using L-SPR measurements. P2VP showed the highest sensibility: for each pH unit, 1 unitis wavelength were shifted. It was also determined the range of salt concentration related with the osmotic regime, unconventional osmotic regime and salted regime transitions for each electrode. The electrodes P2VP, PAA, PDMAEMA and P2VP/PAA were applied as glucose biosensor...